2017
DOI: 10.1016/j.bbrc.2017.10.084
|View full text |Cite
|
Sign up to set email alerts
|

E6AP/UBE3A catalyzes encephalomyocarditis virus 3C protease polyubiquitylation and promotes its concentration reduction in virus-infected cells

Abstract: The encephalomyocarditis virus (EMCV) 3C protease (3Cpro) is one of a small number of viral proteins whose concentration is known to be regulated by the cellular ubiquitin-proteasome system. Here we report that the ubiquitin-conjugating enzyme UbcH7/UBE2L3 and the ubiquitin-protein ligase E6AP/UBE3A are components of a previously unknown EMCV 3Cpro-polyubiquitylating pathway. Following the identification of UbcH7/UBE2L3 as a participant in 3Cpro ubiquitylation, we purified a UbcH7-dependent 3Cpro-ubiquitylatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, throughout evolution viruses have acquired numerous strategies to evade the host immune system (32), notably the type I IFN antiviral response. Previous studies have shown the ability of EMCV to evade host immunity via interfering with IFN signaling (10)(11)(12)(13)(14)(15). To our knowledge, we are the first to show the ability of the EMCV structural protein, VP2, to antagonize the components of the RLR/MDA5 signaling pathway.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, throughout evolution viruses have acquired numerous strategies to evade the host immune system (32), notably the type I IFN antiviral response. Previous studies have shown the ability of EMCV to evade host immunity via interfering with IFN signaling (10)(11)(12)(13)(14)(15). To our knowledge, we are the first to show the ability of the EMCV structural protein, VP2, to antagonize the components of the RLR/MDA5 signaling pathway.…”
Section: Discussionmentioning
confidence: 69%
“…We and others have used HEK293 cells as a model cell line for EMCV infection studies (10,11,35,36). We are aware of the limitation that using this cell line poses as it is inherently virally transformed and expresses the E1A oncogene from adenovirus (Adv) and also the artificial nature of using a cell line model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and VP2, are known to block innate immune signaling pathway activation[5][6][7][22][23][24]. Hostproteins are also involved in EMCV infection.…”
mentioning
confidence: 99%